Two robust metal–organic frameworks with uncoordinated N atoms for CO2 adsorption. Issue 43 (5th October 2015) - Ren, Guo-Jian; Liu, Yan-Qing; Hu, Tong-Liang; Bu, Xian-He
Abstract : Two highly porous metal–organic frameworks are successfully constructed through the assembling of Co/Ni ions and mixed ligands. From the contribution of the uncoordinated tetrazolate N atoms of the ligand the two complexes show high CO2 adsorption capacities, serving as potential CO2 adsorption materials. Abstract : Two highly porous metal–organic frameworks are successfully constructed through the assembling of Co/Ni ions and mixed ligands. From the contribution of the uncoordinated tetrazolate N atoms of the ligand the two complexes show high CO2 adsorption capacities, serving as potential CO2 adsorption materials.